Assessment of active state titin's effects on muscle mechanics using finite element modeling - Çankaya, Alican Onur. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2022., 2022)
Calcium dependent mechanical behaviors characterize titin's contribution to force production in three-myo lament paradigm: (1) Sti ening of PEVK (Proline, Glutamate, Valine, Lysine) segment, and (2) reduction of free-spring length via N2A titin binding. This thesis is focused on the introduction of an alternative perspective to the analysis of titin with incorporating epimuscular myofascial loads. Isolated and integrated rat muscle nite element model variations were used with three titin models: passive state titin, active state titin-I and active state titin-II. Results of isolated model showed that active state titin-I and II limits sarcomere shortening (lm = 32.7mm: up to 10% and 20%, respectively). Such shorter sarcomere e ect characterizes active state titin's mechanism of e ects. Integrated models showed that the shorter sarcomere e ect becomes an inconsistent and variable mechanism: Shorter sarcomere e ect is further enhanced for proximal fascicle interfaces (by 30.2% and 31.0%, respectively) whereas it is also diminished for remaining fascicles (by 10.3% and 14.0%, respectively), but even a longer sarcomere e ect is shown. Overall, titin's mechanism of e ect and functionality are manipulated by epimuscular myofascial force transmission. This implies a new approach for the 3-miyo lament model: For the analysis of the components of the contractile machinery, contribution to force production and contribution to muscle mechanics should be assessed with alternative perspectives. Titin's calcium dependent mechanical behaviors belong to former as these increases its sti ness, whereas shorter sarcomere e ect belongs to latter as this mechanism further translates its e ect to other components as well as to length-force characteristics. These together comprehensively de ne titin's contribution as a third myo lament.|Keywords : Force Enhancement, Titin, Shorter Sarcomere Effect, Epimuscular My ofascial Force Transmission, Epimuscular Myofascial Loads, Finite Element Modeling .
Keywords: Electromotive force.; Finite element method.